ACSM's exercise for older adults - Chodzko-Zajko, Wojtek J. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins, 2014)
'ACSM's Exercise for Older Adults is a new book designed to help health and fitness professionals guide their older clients to appropriate exercise programs'--Provided by publisher.
Understanding human aging -- Physical and psychological benefits of physical activity and exercise for healthy older adults -- Active living - options and benefits for seniors -- Motivating older adults to initiate and maintain a physically acive lifestyle -- Physical activity options for healthy older adults -- Active options for older adults with special issues and concerns -- Assessing physical activity, fitness, and progress in older adults -- Healthy lifestyles in old age: integrating physical activity with nutrition to maintain a healthy body composition and prevent disability -- Helping older adults select the physical activity program that's right for them -- Frequently asked questions about physical activity.
This book includes online access at http://the point.lww.com/active, please refer library staff for the password
Keywords: Physical fitness; Aged; Aging -- Physiological aspects; Exercise for older people